Mitochondrial brain proteome acetylation levels and behavioural responsiveness to amphetamine are altered in mice lacking Sirt3 - Sidorova-Darmos, Elena; Fallah, Merrick S.; Logan, Richard; Lin, Cheng Yu; Eubanks, James H. (Frontiers in Physiology, 2022)
Post-translational modification of mitochondrial proteins represents one mechanism by which the functional activity of mitochondria can be regulated. In the brain, these modifications can influence the functional properties of different neural circuitries. Given that the sirtuin family member Sirt3 represents the primary protein deacetylase enzyme in mitochondria, we tested whether brain mitochondrial proteome acetylation would increase in male or female mice lacking Sirt3. Our results confirm that whole brain mitochondrial proteome acetylation levels are indeed elevated in both sexes of Sirt3-KO mice relative to controls. Consistently, we found the mitochondria of mouse embryonic fibroblast (MEF) cells derived from Sirt3-KO mice were smaller in size, and fewer in number than in wild-type MEFs, and that mitochondrial free calcium levels were elevated within the mitochondria of these cells. As protein acetylation can influence mitochondrial function, and changes in mitochondrial function have been linked to alterations in neural circuit function regulating motor activity and anxiety-like behavior, we tested whether Sirt3-deficient mice would display sensitized responsiveness to the stimulant amphetamine. Both male and female Sirt3-KO mice displayed hyper-locomotion and attenuated anxiety-like behavior in response to a dose of amphetamine that was insufficient to promote any behavioural responses in wild-type mice. Collectively, these results confirm that Sirt3 regulates mitochondrial proteome acetylation levels in brain tissue, and that the absence of Sirt3 increases the sensitivity of neural systems to amphetamine-induced behavioural responses.